Industrial training report: University Malaysia Kelantan, Jeli Branch / Muhammad Rifaie Mohd Nadzri - Mohd Nadzri, Muhammad Rifaie (Perpustakaan Tengku Anis, 2017)
This special project based on the period from 1st February 2017 until 3dh June 2017 in Faculty of Agro-Based Industry (FIAT) at Universiti Malaysia Kelantan (UMK). The trainee being placed in FIAT under the supervision of Dr Leony Tham Yew Seng which is senior lecturer in that campus. The trainee is assigned to held a workshop as the special project which is Appsheet Workshop fir final year student. Basically, trainee supervisor has being thinking to use a new platform in managing his final year student final project by key in their project data in the mobile apps. Right now, the workflow is still using the manual/ way which is student need to key in into the sheed of paper before it being transfer into document so that is such an ineffective way. Other than that, during this practical training program, trainee also joining a few activities that being held by department of library in UMK Jeli Campus which each of them gave a new experience and gained a lot of knowledge. Throughtout the industrial training session, the trainee had improved a lot of skills such as communication skill, problem solving, self learning, teamwork and others. The industrial session program are going well until the end of the day. The staff in Universiti Malaysia Kelantan (UMKJ Kampus Jeli gave a very good cooperation with the trainee during the industrial training session.